Socioeconomic context of water, sanitation and hygiene practices in Delta, Edo and Ekiti States, Nigeria (2016)
Understanding issues related to Water, Sanitation and Hygiene (WASH) practices has become more critical in Nigerian communities in view of the increasing prevalence of diseases due to lack of safe water and poor hygiene behavior in the country. This cross-sectional exploratory survey employed intra-method triangulation to collect data through In-depth Interviews, Focus Group Discussions and Unobtrusive observation from purposively selected communities in Delta, Edo and Ekiti states. Findings reveal that communities are willing to pay for WASH services insofar as the payment will add value to their lives; the rate of community participation and performance in WASH activities is a function of active mobilization of the people and effective monitoring of WASH committee members. In view of the benefits of cleanliness for a healthy population, continuous education and sensitization of the people on WASH should be sustained in relevant communities.